Anthropometric Assessment for Adolescent Pregnancy: A Descriptive Study on Married Adolescents in Bangladesh - Haque, MN (Journal of Nepal Paediatric Society, 2010)
Background: Adolescent childbearing has emerged as a major concern in Bangladesh due to its shorter term adverse effects on both the mothers and babies born to adolescent mothers. Bangladesh is one of the vulnerable countries in the world and the most vulnerable country in South Asian region regarding early motherhood risks. Most of the adolescents pelvis is not mature enough for childbirth and malnutrition may stunt normal growth of adolescent women. But a greater proportion of currently married adolescent women want a child very soon. Hence it is needed to assess adolescent women’s physical and nutritional status for making future pregnancy outcomes safer. Objectives: This study aims to evaluate the physical and nutritional status of married adolescent women for pregnancy by calculating prevalence of low weight, low height, stunting and thinness. Methodology: For assessing pre-pregnancy physical and nutritional status of married adolescent women, data extracted from Bangladesh Demographic and Health Survey (BDHS)–2004. Based on fundamental anthropometric variables (weight and height), stunting and thinness profile of study population has been prepared. Also, group mean of weight and height, prevalence of low weight (<45kg) and low height (<145 cm) have been calculated. Results: Adolescent women, on average, are at vulnerable for childbirth regarding their weight in the study results. For instance, more than 64% of married non-pregnant adolescent women’s weights are less than 45 kg and more than 15% of married non-pregnant adolescent women belong to height less than 145 cm in Bangladesh. It is also estimated that more than 16% and around 50% of married non-pregnant adolescent women were thin and stunted respectively in Bangladesh. Conclusion: Since early childbearing is a social norm in Bangladesh and many of married adolescent women are not physically fit for pregnancy, so it is necessary to encourage married adolescent women to delay childbearing through community education and by encouraging them to use family planning services. It should be necessary to pay special emphasizes for improving adolescent women’s nutritional status through the country’s Health, Nutrition and Population Sector Program or through National Nutrition Program (NNP). Keywords: Adolescent; Bangladesh; Pregnancy; Stunting; Thinness DOI: 10.3126/jnps.v30i3.3918 J Nep Paedtr Soc 2010;30(3):154-159